New approaches, bioavailability and the use of chelates as a promising method for food fortification. (30th March 2022) - Mattar, Ghadeer; Haddarah, Amira; Haddad, Joseph; Pujola, Montserrat; Sepulcre, Franscesc
Highlights: Chelation protects minerals from inhibitors increasing bioavailability by 2–3 times. Chelated mineral complexes are promising fortifiers, but their cost limits their use. Chelation overcomes instability of encapsulation and unproven safety of nanoparticles. Comparing three innovative fortifiers, the optimum appeared to be mineral chelates. Abstract: Food fortification has been used for many years to combat micronutrient deficiencies; the main challenge with food fortification is the combination of a bioavailable, affordable fortificant with the best (food) vehicle as a carrier to reach at-risk populations. This paper considers mineral deficiencies, especially iron, food fortification, target populations, and the use of chelates in food fortification, as well as different types of mineral-chelate complexes, advantages and limitations of previous trials, methods used for analysis of these complexes, bioavailability of minerals, factors influencing it, and methods particularly those in vitro for predicting outcomes. Three innovative methods (encapsulation, nanoparticulation, and chelation) were explored, which aim to overcome problems associated with conventional fortification, especially those affecting organoleptic properties and bioavailability; but often lead to the emergence of new limitations (for example instability, impracticality and high costs) requiring further research.